Fiscal Consolidation and Economic Growth: Insights from the Case of Pakistan (The Pakistan Development Review, 2017)
The primary objective of this paper is to find whether fiscal consolidation has positive impact on economic growth in Pakistan or not, using nonlinear specification. In addition to checking nonlinear relationship between fiscal deficit and economic growth, we also compute optimal level of fiscal deficit that enhances growth, using data from 1976 to 2015. The results show that at the current level, fiscal deficit is positively associated with economic growth but fiscal deficit at a very high level would be damaging for growth. The nonlinear association between fiscal deficit and economic growth suggests that Pakistan would need to keep fiscal deficit in check and keep on practicing fiscal prudence. The analysis of data reveals that although the fiscal deficit has come down over the years, capital, or development, expenditures have also come down. According to the calculations in this paper, the optimal level of fiscal deficit is 0.74 percent of GDP, implying that Pakistan’s expenditure composition and tax structure needs to be revisited to achieve higher economic growth. JEL Classifications: 2SLS Keywords: Economic Growth, Fiscal Consolidation